Gentamicin Release from Bone Cement: A Comparative Study between Hand Made Liquid & Powder Gentamicin beads - Parnmanee, MD, Surasit (Journal of Southeast Asian Orthopaedics, 2022)
Background and Purpose: Gentamicin beads are widely used in treatment of bone and joint infections. The commercial form is expensive and may be unavailable in most hospitals in Thailand. Most orthopaedic surgeons make them from gentamicin and powdered bone cement, but this still has high costs. In this study, the author used liquid gentamicin, which was used regularly in intravenous route, to mix in bone cement and compare gentamicin release between handmade liquid and powder gentamicin beads. Methods: A prospective randomized clinical trial in patients with bone and joint infections from bacterial causes in Hatyai Hospital. Patients were divided into liquid gentamicin and powder gentamicin groups. Gentamicin concentration in surgical areas were collected, compared, and analyzed. Results: Thirty patients in each group who had bacterial bone and joint infections were treated with bone debridement and gentamicin beads were placed in surgical area. The liquid gentamicin group resulted in significantly higher levels than in the powder group. Both groups had gentamicin levels many times higher than the minimal inhibitory concentration (MIC) and persisted for at least 28 days. Clinical results of both groups were excellent and no renal toxicity was observed. Conclusions: The liquid gentamicin group had more antibiotic released to the surgical area than the powder group, no renal toxicity detected, and appears to be cost-effective in the treatment of bacterial bone and joint infections.